2009
DOI: 10.1111/j.1570-7458.2009.00872.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vegetation density, height, and connectivity on the oviposition pattern of the leaf beetle Galeruca tanaceti

Abstract: Vegetation structure can profoundly influence patterns of abundance, distribution, and reproduction of herbivorous insects and their susceptibility to natural enemies. The three main structural traits of herbaceous vegetation are density, height, and connectivity. This study determined the herbivore response to each of these three parameters by analysing oviposition patterns in the field and studying the underlying mechanisms in laboratory bioassays. The generalist leaf beetle, Galeruca tanaceti L. (Coleoptera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 45 publications
(65 reference statements)
0
23
0
Order By: Relevance
“…These changes in plant quality and quantity should affect the abundance of insect herbivores that feed on thistles. Larger plants may sustain higher herbivore densities or be more attractive for female's oviposition [39], and enhanced plant quality improves herbivores' development rate, survival and/or fecundity, thus increasing their abundance [40,41]. Accordingly, we found that refuse dump thistles had higher aphid density than those established on adjacent soils.…”
Section: Discussionmentioning
confidence: 65%
“…These changes in plant quality and quantity should affect the abundance of insect herbivores that feed on thistles. Larger plants may sustain higher herbivore densities or be more attractive for female's oviposition [39], and enhanced plant quality improves herbivores' development rate, survival and/or fecundity, thus increasing their abundance [40,41]. Accordingly, we found that refuse dump thistles had higher aphid density than those established on adjacent soils.…”
Section: Discussionmentioning
confidence: 65%
“…Earlier field investigations in this parasitoid‐host system showed that host egg clutches are deposited more frequently in patches with high stem density than compared with low density patches (Meiners & Obermaier, 2004; Randlkofer et al , 2009). Moreover, the success of O. galerucivorus to parasitise eggs is reduced within patches of tall and dense vegetation on a small spatial scale in the field (r = 0.1 m ) (Obermaier et al , 2008).…”
Section: Discussionmentioning
confidence: 78%
“…1.5 mm in size) mostly walk up and down plants during their search for host eggs. In general, the probability of leaf beetle oviposition increases in patches with high stem density in the field (Meiners & Obermaier, 2004; Randlkofer et al , 2009). Earlier field studies also revealed that a dense and complex vegetation structure reduces the parasitism success of the egg parasitoid on a small spatial scale ( r = 0.1 m ) (Obermaier et al , 2008).…”
Section: Introductionmentioning
confidence: 99%
“…; Randlkofer et al. ). Another factor that affects parasitism levels is the density of the respective host (Cloyd and Sadof ; Hancock et al.…”
Section: Discussionmentioning
confidence: 97%